Haunted dreams : fantasies of adolescence in post-Soviet culture - Kaminer, Jenny (NIU series in Slavic, East European, and Eurasian studies., 2022)
"This book analyzes representations of adolescence in Russian culture-including in prose, film, drama, and television-in the period since the end of the Soviet Union in 1991"--